Extraction of Li and Co from industrially produced Li-ion battery waste – Using the reductive power of waste itself. (15th July 2019) - Peng, Chao; Liu, Fupeng; Aji, Arif T.; Wilson, Benjamin P.; Lundström, Mari
Highlights: Metallic components present in LIBs waste can enhance Co and Li leaching. Cu/Al-rich separation overflow additions augment acid spent LIBs leaching. >99% of Li and Co can be extracted by addition of Al/Cu containing fractions. Presence of Fe can promote the dissolution of both LiCoO2 and Cu (Al). Co and Li present in overflow fractions can be recovered simultaneously. Abstract: Industrially produced spent lithium-ion batteries (LIBs) waste contain not only strategic metals such as cobalt and lithium but also impurity elements like copper, aluminum and iron. The current work investigates the distribution of the metallic impurity elements in LIBs waste, and their influence on the acid dissolution of target active materials. The results demonstrate that the presence of these, naturally reductive, impurity elements (e.g. Cu, Al, and Fe) can substantially promote the dissolution of active materials. Through the addition of Cu and Al-rich larger size fractions, the extraction efficiencies of Co and Li increased up to over 99%, to leave a leach residue that is rich in graphite. By this method, the use of high cost reductants like hydrogen peroxide or ascorbic acid could be avoided. More importantly, additional Co and Li associated with the Cu and Al electrode materials could be also recovered. This novel approach contributes not only to improved reduction efficiency in LIBs waste leaching, but also to improved total recovery of Co and Li from LIBs waste, even from the larger particle size fractions, which are typically lost from circulation.